Tuning the thermal expansion behavior and promoting the mechanical properties of Mg–9Al–1Zn magnesium alloys by the introduction of MnCoGe-based alloys. (June 2022) - Wu, Sujuan; Zhou, Daiqi; Huang, Yadong; Wang, Ke; Song, Jiangfeng; Dong, Zhihua; Jiang, Bin
Abstract: The mismatch of thermal expansion in Mg and Al/Cu alloys may cause flaking or destruction at a joint interface, and further restrict their service life and practical application. Combining the negative thermal expansion materials could reduce the thermal expansion of Mg alloys, but destroy their ductility. In this study, we overcome this challenge by the combination of MnCoGe-based alloys with Mg–9Al–1 Zn Mg alloys. The addition of less than 7 wt% Mn0.98 CoGe has shown matched coefficient of thermal expansion of Cu alloys, and moderated strength and plasticity. Due to the inconsistency with the predicted values, we figured out the critical mechanism on both thermal expansion regulation and mechanical property improvement is attributed to the secondary phases and the metallic bonding interfaces. These Mg alloys with low thermal expansion and good mechanical properties could be useful to the electronic packaging and precision fields. Graphical abstract: Image, graphical abstract